2021
DOI: 10.1093/mnras/stab3191
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the water and carbon dioxide production rates of Comet 67P/Churyumov–Gerasimenko

Abstract: The European Space Agency Rosetta/Philae mission to Comet 67P/Churyumov–Gerasimenko in 2014–2016 is the most complete and diverse investigation of a comet carried out thus far. Yet, many physical and chemical properties of the comet remain uncertain or unknown, and cometary activity is still not a well-understood phenomenon. We here attempt to place constraints on the nucleus abundances and sublimation front depths of H2O and CO2 ice, and to reconstruct how the nucleus evolved throughout the perihelion passage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 114 publications
4
57
0
Order By: Relevance
“…We now consider the presence and survival of CO 2 ice in coma chunks. Davidsson et al (2020) reproduced the observed pre-perihelion CO 2 production rate curve of 67P from 3.5 AU to 1.24 AU with a NIMBUS model that had the perihelion CO 2 sublimation front located ∼ 1.9 m below the surface near the equator, and where that depth diminished with latitude to ∼ 0.2 m at the south pole. If the suggested presence of CO 2 ice at shallow depths is correct, it is conceivable that regular sublimation-driven activity occasionally can expel extremely cold chunks containing supervolatiles at perihelion.…”
Section: Volatile Loss During the Transfer Through The Comasupporting
confidence: 55%
See 1 more Smart Citation
“…We now consider the presence and survival of CO 2 ice in coma chunks. Davidsson et al (2020) reproduced the observed pre-perihelion CO 2 production rate curve of 67P from 3.5 AU to 1.24 AU with a NIMBUS model that had the perihelion CO 2 sublimation front located ∼ 1.9 m below the surface near the equator, and where that depth diminished with latitude to ∼ 0.2 m at the south pole. If the suggested presence of CO 2 ice at shallow depths is correct, it is conceivable that regular sublimation-driven activity occasionally can expel extremely cold chunks containing supervolatiles at perihelion.…”
Section: Volatile Loss During the Transfer Through The Comasupporting
confidence: 55%
“…Alternatively, they may have originated from underneath the airfall layer. NIMBUS simulations by Davidsson et al (2020) show that the measured pre-perihelion CO 2 production rate curve is reproduced when the depth of the CO 2 sublimation front is located 3.8 m below the surface on the northern hemisphere, and at 1.9 m below the surface on the southern hemisphere at aphelion (these depths are modified in the model over time because of dust mantle erosion as well as CO 2 sublimation, see Sec. 3.2).…”
Section: Discussionmentioning
confidence: 97%
“…Migliorini, A. et al 2016;Gasc et al 2017) discovered spatial and temporal variations in the coma H 2 O/CO 2 ratios, implying non-uniform mixing ratios for these two volatiles within the nucleus. As shown by Davidsson et al (2021Davidsson et al ( , 2022 for 67P, this could be caused by physical/chemical evolution of the comet's surface layers due to anisotropic illumination of the comet, but primordial variations in the H 2 O/CO 2 ratio intrinsic to the nucleus are also possible. It is therefore plausible that CH 3 OH in C/2016 R2 exists as a component within an apolar ice matrix dominated by CO and CO 2 , and some of this CH 3 OH is released into the coma when CO sublimates (as observed).…”
Section: Comparison With Previous Observations Of This Cometmentioning
confidence: 99%
“…Most thermophysical models of nuclei rely on the assumption of dry mantles (where water-ice sublimation is assumed to be negligible) enveloping nuclei rich in ices (Keller et al 2015 ;Davidsson et al 2022 ). Ho we ver, a dry crust or mantle where water-ice sublimation is assumed to be negligible is inconsistent with the definition itself of a comet, i.e.…”
Section: Ac T I V I T Y M O D E L B E Yo N D 4 Aumentioning
confidence: 99%
“…Also the observed evolution of the nucleus colour of Comet 67P/Churyumov-Gerasimenko excludes the presence of any ices-depleted crust (Ciarniello et al 2022 ). Models based on a crust where water-ice sublimation is assumed to be negligible (Davidsson et al 2022 ) are inconsistent with the measured 67P Hapi's erosion (Cambianica et al 2020 ), so that they cannot constrain the nucleus refractory-to-water-ice mass ratio δ w . They also require ad-hoc changes of the thickness of the dry crust enveloping the entire nucleus (Skorov et al 2020 ) to fit the observed time evolution of the gas loss rates (L äuter et al 2020 ).…”
Section: Ac T I V I T Y M O D E L B E Yo N D 4 Aumentioning
confidence: 99%